Adoption of sustainable agricultural practices in Brazil: understanding the influence of socioeconomic and psychological factors. Issue 2 (8th June 2021) - Foguesatto, Cristian Rogério; Machado, João Armando Dessimon
Abstract : Purpose: Despite substantial efforts made by Brazil's government to increase the adoption rate of sustainable agricultural practices (SAP), many of them have not been adopted by the farmers. This paper explores the factors influencing the adoption of SAP in the state of Rio Grande do Sul, one of the largest Brazilian grain producers. Design/methodology/approach: Using four logistic models, the authors test a conceptual framework that provides a systemic view of farmers' adoption decisions from a sample of 172 farmers. Findings: The findings show that the adoption of SAP is influenced by farmers' socioeconomic characteristics (e.g. gender, level of education, farm size, asset values and farm income), attributes of SAP (compatibility of agricultural practice) and psychological factors (ecocentrism, anthropocentrism, and beliefs about climate change). Research limitations/implications: The results presented may not reflect the characteristics of the region studied because random sampling was not employed. Also, other psychological statements should be used in the questionnaire. Originality/value: Little attention has been given to the analysis of farmers' psychological factors in studies on the adoption of agricultural conservation practices. This study provides a "systemic approach" that measures both socioeconomic and psychological factors.